IJIMAI Editor's Note - Vol. 3 Issue 3 - Montenegro-Marin, Carlos Enrique (International Journal of Interactive Multimedia and Artificial Intelligence (IJIMAI), 2020)
The research works presented in this issue are based on various topics of interest, among which are included: 3D Interface, Information Extraction, Artificial immune system, Security in Cloud Computing, Genetic Algorithm, Activity recognition, 3D Render Distribution, Software visualization, Event Perception, New Programming Language, Distributed computing, MOOC environments, etc.
Keywords: editors note; IJIMAI